2016
DOI: 10.3389/fncel.2016.00188
|View full text |Cite
|
Sign up to set email alerts
|

Glia: A Neglected Player in Non-invasive Direct Current Brain Stimulation

Abstract: Non-invasive electrical brain stimulation by application of direct current (DCS) promotes plasticity in neuronal networks in vitro and in in vivo. This effect has been mainly attributed to the direct modulation of neurons. Glia represents approximately 50% of cells in the brain. Glial cells are electrically active and participate in synaptic plasticity. Despite of that, effects of DCS on glial structures and on interaction with neurons are only sparsely investigated. In this perspectives article we review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
99
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 90 publications
6
99
1
1
Order By: Relevance
“…Several models have demonstrated the direct modulation of plasticity, inflammation, neurogenesis and cerebrovascular functions by glial cells following neurostimulation 118,127 . For example, stimulation evokes astrocyte-induced cortical plasticity, as demonstrated in studies using transcranial direct current stimulation (tDCS) 128 .…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models have demonstrated the direct modulation of plasticity, inflammation, neurogenesis and cerebrovascular functions by glial cells following neurostimulation 118,127 . For example, stimulation evokes astrocyte-induced cortical plasticity, as demonstrated in studies using transcranial direct current stimulation (tDCS) 128 .…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
“…Implanted-electrode stimulation upregulates inflammatory receptors (toll-like receptors) in microglia 131 , favouring a shift to a proinflammatory state 117 . However, the timing 132 and intensity 133 of stimulation may differentially affect reactivity and inflammation, suggesting a gradient of glial responses 127 . In the context of neurogenesis, neuromodulation is gaining traction as a reparative tool for brain injury and disease 118,134 .…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
“…However, damage was not consistently observed for 0.5 mA cathodal and 1.0 mA anodal stimulation groups (Pikhovych et al, 2016a, Pikhovych et al, 2016b), which indirectly suggests a role for polarity. More recently, lesions have been reported at an anodal current intensity of 0.6 mA (47.8 A/m 2 electrode current density) (Gellner et al, 2016), suggesting the lesion threshold in rats may be lower than previously reported. Rodent studies evaluating tDCS safety through microglial analysis have shown microglial activation can occur after anodal or cathodal stimulation at 0.5 mA for 15 minutes (Rueger et al, 2012) (c.f.…”
Section: Introductionmentioning
confidence: 91%
“…(Liebetanz et al, 2009). Microglial changes in morphology associated with neurodegeneration after anodal tDCS have been reported at current intensities as low as 0.4 mA (31.8 A/m 2 electrode current density) (Gellner et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation